2016
DOI: 10.4240/wjgs.v8.i8.583
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy: A study from India on the impact of evolution from a low to a high volume unit

Abstract: The transformation from a low volume to a high volume provider of PD resulted in most favourable outcomes favouring the continued centralization of this high risk procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The reported postoperative fistula rates at three other centers from India were 15%, 15.39%, and 12% respectively, 24–26 and the fistula rate at our center was 17.0%. Studies have shown that high volume centers and high volume surgeons provide best outcomes after pancreaticoduodenectomy 25,27,28 .…”
Section: Discussionmentioning
confidence: 44%
“…The reported postoperative fistula rates at three other centers from India were 15%, 15.39%, and 12% respectively, 24–26 and the fistula rate at our center was 17.0%. Studies have shown that high volume centers and high volume surgeons provide best outcomes after pancreaticoduodenectomy 25,27,28 .…”
Section: Discussionmentioning
confidence: 44%
“…There is a growing but stable trend in achieving acceptable and comparable outcomes in community hospitals adopting pancreatic surgery. This is largely due to high-volume experienced surgeons migrating to community hospitals, and thus altering these institutions' status into high-volume hospitals [11,13,32,37].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer remains one of the cancers with the poorest prognosis, with an overall 5-year survival rate of about 5%, without much difference between high-income countries and low-income and middleincome countries [1]. Pancreaticoduodenectomy (PD) is a complex, high-risk surgical procedure usually performed for malignancy of the pancreatic head or periampullary region [2].…”
Section: Introductionmentioning
confidence: 99%
“…Major postoperative complications include: pancreatic leak or stula, intra-abdominal abscess, bile leak, postoperative hemorrhage requiring blood transfusion or re-exploration, delayed gastric emptying, and complications related to the surgical site such as infection and wound dehiscence [6]. Various studies have demonstrated that high volume tertiary centers have signi cantly lower (< 5%) in-hospital mortality rates for pancreaticoduodenectomy than the low volume centers (> 10%) [2]. We set out to conduct this systematic research to link our evidence regarding the volume of cases and outcome at tertiary care center in underdeveloped country and to implement the data to improvise our practice in managing such patients, and analyze the impact of turning our department from a medium to a high volume care provider of PD.…”
Section: Introductionmentioning
confidence: 99%